Angiotensin converting enzyme-2 as therapeutic target in COVID-19. Issue 4 (July 2020) - Roshanravan, Neda; Ghaffari, Samad; Hedayati, Mehdi
Abstract: The pandemic of coronavirus disease 2019 (COVID-19) is a global health emergency that poses a significant threat to world people's health. This outbreak causes major challenges to healthcare systems. Given the lack of effective treatments or vaccine for it, the identification of novel and safe drugs against COVID-19 infection is an urgent need. Angiotensin-converting enzyme 2 (ACE2) is not only an entry receptor of the SARS-CoV-2 virus, the virus that causes COVID-19, but also can protect from lung injury. In this view, we highlighted potential approaches to address ACE2-mediated SARS-CoV-2 virus, including 1) delivering an excessive soluble form of ACE2 (recombinant human ACE2: rhACE2) and 2) inhibition of the interaction between SARS-CoV-2 virus and ACE2 by some compounds with competitive effects (morphine and codeine). Further clinical trials in this regard can reveal a more definite conclusion against the COVID-19 disaster. Highlights: The outbreak of COVID-19 has been identified by the World Health Organization as a global pandemic. Angiotensin Converting Enzyme-2 can be considered as a therapeutic target in COVID-19. Recombinant human ACE2, morphine and codeine may be considered as novel therapeutic approaches for COVID-19.